2016
DOI: 10.1515/ausal-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Market orientation of the Hungarian SMEs working in the meat processing and dairy industries

Abstract: We are looking for the answer as to what tendencies were indicative of the future development of required marketing activity of the SMEs in the article dealing with the marketing activity of the SMEs working in the food industry. The article is based on a nationwide survey among 200 SMEs working in the food processing industry. In this article, we focus on the SMEs working in the dairy and meat processing industries. The results of the nationwide research and some domestic references refer to that there is a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The results indicate that there is a positive, medium-strength linear relationship between corporate performance dimensions and the dimensions of market orientation; therefore, hypothesis H2 is confirmed. This result supports not only domestic research, but also many international results (Polereczki et al, 2012;Polereczki, Kövér, Bareith, and Szakály, 2013;Kovács, Szakály and Polereczki, 2016;Kis, Kovács and Szakály, 2020;Kontor 2014b;Armario et al, 2008).…”
Section: The Examination Of Corporate Performance Dimensions and The ...supporting
confidence: 84%
See 1 more Smart Citation
“…The results indicate that there is a positive, medium-strength linear relationship between corporate performance dimensions and the dimensions of market orientation; therefore, hypothesis H2 is confirmed. This result supports not only domestic research, but also many international results (Polereczki et al, 2012;Polereczki, Kövér, Bareith, and Szakály, 2013;Kovács, Szakály and Polereczki, 2016;Kis, Kovács and Szakály, 2020;Kontor 2014b;Armario et al, 2008).…”
Section: The Examination Of Corporate Performance Dimensions and The ...supporting
confidence: 84%
“…However, the market orientation research in the food industry in Hungary has concluded that there is a moderately strong positive connection between the adapted level of market orientation and corporate performance. (Polereczki et al, 2012;Polereczki, Kövér, Bareith, and Szakály, 2013;Kovács, Szakály and Polereczki, 2016;Kis, Kovács and Szakály, 2020). Appendix 1 contains more research examining the connection between market orientation and corporate performance.…”
Section: Discussionmentioning
confidence: 99%